PENINGKATAN HASIL BELAJAR LUAS TRAPESIUM DAN LAYANG-LAYANG DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS V SD - Oktavia, Latifah Ningsih (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research early from fact in elementary school that study is there isn’t discus in the class with specialist, so there is noresponsibility of allmembers ofthe groupto thematerial being studiedand the resultinglow learning outcomes. This research isan act of class study using qualitative and quantitative approaches. Cooperative learning model Jigsaw requiresthe involvementand responsibility and interdependence of allmembers ofthe group. Results showed improved learning outcomes spacious trapezoid and kite first cycle with an average value of49.37cognitive, affective value average 72.26, and the average value of psychomotor 74. Then in the second cycle ofthe averag evalue of 81 cognitive, affective value ​​average 82.5, and the average value of psychomotor 82.91. Keywords:academic achievement; cooperative learning model jigsaw